Physical activity patterns during school recess : a study in children 6 to 10 years old - Lopes, Vítor Pires (2006)
The aims of this study were to characterize the spontaneous physical activity of children during school recess, and to estimate variation in physical activity associated with gender and age. A MTI actigraph (Model 7164) was used with a sample of 140 boys and 131 girls, 6 to 10 years of age. MTI counts were converted to METs using a regression equation developed for children. The number and average duration of periods of activity by intensity were calculated for each child during a 30 minute recess: rest or mild physical activity (≤ 2.9 METs), moderate physical activity (3.0-5.9 METs,), vigorous physical activity (6.0-8.9 METs) and very vigorous physical activity (≥ 9.0 METs). Boys and girls spent about 50% of the recess in physical activity. Physical activity was characteristically done in very short bursts with intervals of rest or mild physical activity. The number of episodes of physical activity of all intensity levels was lower in older children while the inverse occurred at rest or mild physical activity. Boys engaged in higher intensity activity than girls and in general spent more recess time in physical activity.